(3RGO GdeSJbfY aj GNJUGQ GdebfYs - (3GdMLGhj, ehSi Hf CMeO Hf ehSi J (B968 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg MeOG dG jfaO CeG HYO agPG eNJUQ aj Gdabg ef ebfY GdEeGe CHh eMeO aj ePgH GdEeGe CMeO cJGH GdWgGQI hgj GQJaGY GdMOKs
(3BNQgG (B:s
(3aEPG HdZ GdMjWI GdJaJ jejfG hTeGdG hdG jRjd bOejg hjLYd EUHYjg aj CPfjg hjJQSd aj GdBPGf hjMOQ aj GdEbGeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 320s
(3eYLe GdeDdajf (B3 / 929s
(3EjVGM Gdecfhf (B1 / 607s
(3TPQGJ GdPgH (B8 / 327s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs